Epistemología para el mal. Saberes psi, autoridad y experticia en la locura (2023)
The present study suggest that evil of modern man is represented by a particular epistemology, which was set forth by german philosopher Immanuel Kant; to support this approach, the analysis start at Kant’s Copernican turn metaphor and emphatizes the importance of the contributions made by this philosopher. From that point it will be developed a second thesis: That the “psi sciences”, are a kind of expert and authorized knowledge to enunciate the truths about madness in the West, pointing out that such knowledge is based on the foundations of Kantian epistemology. This last approach involves a reflection on ethical positions and policies about disciplines such as psychology and psychiatry, and is related to their practices of social normalization, in this order of ideas the role of the technique and the role of the psi scientist in the contemporary world are critically analyzed. © 2020, Universidad del Zulia. All rights reserved.